Resisting, demanding, negotiating and being: The role of scandals in the everyday lives of Argentinean travestis - Cutuli, Maria Soledad (2012)
The aim of this article is to explore the different uses and meanings of the category ‘scandal’ among Argentinean travestis. It is argued that this insight could be fruitful to understand the logic according to which local travestis resist, negotiate, demand and manage access to rights, opportunities, and/or goods, from which they have been historically excluded due to their non-hegemonic gender identities. In line with the performative logic employed to construct their gender identities, the idea of ‘scandal’ is fruitful for them to think, to make themselves visible and to act politically. This article proposes a political and anthropological approach to study the relation between structures of inequality and resistance through collective action. It takes into account a perspective developed by political anthropologists, centered in the power relationships analysis and an understanding of politics as a dimension of daily life.